THE ONE SHOW JUGDGED TO BE ADVERTISINGS BEST PRINT, RADIO,TV. - GOLDSMITH, GARY (Singapour, 1996)
1.Board of directors presidents message one show judges one club members 1996 gold , silver and bronze awards / 2.Best of show / 7.The gold award winners on the gold award winners 1996 print finalists / 8.Consumer newpaper / 9.consumer magazine / 10.Outdoor / 11.Trade / 12.Collateral / 13.1996 public service - political finalists / 14.1996 radio finalists / 15.1996 television finalists / 16.1996 interactive finalists / 17.1996 college finalists
Incluye indice onomastico pag.611
Keywords: DISEÑO GRAFICO